Identifying sensory attributes of Korean rice wine ( makgeolli ) using sensory evaluation and chemical analysis - Wong, Barry; Owens, Adrian; Phillips, Megan; Kam, Rothman (Journal of food science, 2023)
Makgeolli is a traditional alcoholic beverage in Korea; however, research on makgeolli is limited in foreign markets such as New Zealand. This study seeks to identify sensory descriptors that best describe makgeolli among New Zealand consumers. Four methods of making makgeolli have been identified based on different processing times and the number of fermentation stages. Chemical analysis and sensory evaluation were carried out to establish the different sensory and flavor properties of the four different makgeolli samples. Chemical analysis using SPME–GC–MS was employed to understand the volatile compounds present in the four makgeolli samples, while two sensory tests were carried out simultaneously using Check‐All‐That‐Apply (CATA) and Just‐About‐Right (JAR). A total of 45 volatile compounds were identified using SPME–GC–MS, and examples of major volatiles include 2‐methyl‐1‐propanol (alcoholic flavor), limonene (citrus‐like flavor), and hexanal (green/grass‐like flavor). One hundred and twenty‐nine subjects (n = 68 females) completed the sensory evaluation and were analyzed for this study. Female subjects tend to rate overall acceptance of makgeolli higher than male subjects; both subjects preferred 1SF‐YN with the highest mean hedonic score, and the least preferred makgeolli was 1SF‐N. From CATA, attributes such as apple, apricot, peach, sweet taste, and bubbly texture were statistically significant when describing makgeolli. For JAR, a high proportion of subjects indicated that sourness was too much in three of the four makgeolli samples.Practical ApplicationResearch on rice wine in Western markets such as New Zealand is limited, and this study gives insight into how New Zealand consumers perceive Korean rice wine (makgeolli). Sensory participants in this study indicated that makgeolli is too sour and lacks sufficient sweetness in the majority of the samples examined. When launching makgeolli to the New Zealand market, practitioners need to optimize sweetness and reduce sourness to increase overall liking. Sensory terms used by subjects describing makgeolli include cider, apple, and sour.